PENGARUH FOOT MASSAGE TERHADAP KUALITAS TIDUR PADA PASIEN RAWAT INAP: - - Dian Mayasari; Fransisca Anjar Rina Setyani; Herlin Lidya (Jurnal Keperawatan Malang, 2025)
Background: Many patients who undergo hospitalization experience sleep disturbances. Sleep disturbances can be caused by service routines, environment, illness and stress. Not fulfilling quality sleep can be a trigger for imbalance because the body's restorative function is not maximized which can have an impact on disease and disorders in the body. Complementary foot massage therapy is one therapy that can improve sleep quality. Purpose: This study aims to determine the effect of giving foot massage on the quality of sleep of inpatients at hospital. Methods: This study used a quasi experimental design with a sampling method using purposive sampling. The sample in this study amounted to 20 respondents in each control group and intervention group. Result: The results of data analysis with the Independent T Test test obtained a p value of 0.045 (p> 0.05), which means that there is a significant difference in the quality of sleep of inpatients at hospital before and after the foot massage intervention. Implication: Foot massage therapy can be one of the independent nursing actions to help improve sleep quality in patients undergoing hospitalization. Keywords: foot massage; hospitalization, sleep quality